Одноконтурное активное экранирование магнитного поля, создаваемого в жилой зоне несколькими воздушными линиями электропередачи - Кузнецов, Б.И.; Никитина, Т.Б.; Волошко, А.В.; Бовдуй, И.В.; Виниченко, Е.В.; Кобылянский, Б.Б. (Електротехніка і електромеханіка, 2018)
Получил дальнейшее развитие метод синтеза систем активного экранирования магнитного поля, генерируемого несколькими воздушными ЛЭП, на основе многокритериального подхода. При синтезе используется упрощенная математическая модель магнитного поля, генерируемого несколькими воздушными ЛЭП, идентификация которой выполнена по экспериментальным значениям индукции магнитного поля в заданных точках на основе решения задачи оптимизации. Приведены результаты синтеза одноконтурной системы активного экранирования магнитного поля,
генерируемого несколькими воздушными ЛЭП. Показана возможность уменьшения индукции магнитного поля с помощью синтезированной системы до уровня санитарных норм Украины. Отримав подальший розвиток метод синтезу систем активного екранування магнітного поля, яке генерується кількома повітряними ЛЕП, на основі багатокритеріального підходу. При синтезі використовується спрощена математична модель магнітного поля, що створюється кількома ЛЕП, ідентифікація якої виконана за експериментальними
значеннями індукції магнітного поля в заданих точках на основі рішення задачі оптимізації. Наведені результати
синтезу одноколової системи активного екранування магнітного поля, яке генерується декількома повітряними ЛЕП.
Показана можливість зменшення індукції магнітного поля за допомогою синтезованої системи до рівня санітарних
норм України. Purpose. The synthesis of active screening system of magnetic field,
generated by several high voltage overhead transmission lines, with
the help of single compensation cables is presented. Methodology.
The initial parameters for the synthesis of active screening system
parameters are the location of the high voltage overhead transmission lines with respect to the protected transmission line space,
geometry and number of cables, operating currents, as well as the
size of the protected space and normative value of magnetic flux
density, which should be achieved as a result of screening. The
objective of the synthesis of the active screening system is to determine their number, configuration, spatial arrangement, wiring diagrams and compensation cables currents, setting algorithm of the
control systems as well as the resulting value of the induction magnetic field at the points of the protected space. Synthesis of active
screening system is reduced to the problem of multi objective
nonlinear programming with constraints in which calculation of the
objective functions and constraints are carried out on the basis of
the Maxwell equations solutions in the quasi-stationary approximation. The problem is solved by a stochastic multi swarm multi agent
particles optimization, which can significantly reduce the time to
solve it. Results. Active screening system synthesis results for reduction of a magnetic field generated by several high voltage overhead
transmission lines are presented. The possibility of a significant
reduction in the level of source magnetic flux density within a given.
Originality. For the first time the synthesis of the active screening
systems of magnetic field generated by the several high voltage
overhead transmission lines within a given region of space is carried out. Practical value. Practical recommendations on reasonable
choice of the number and spatial arrangement of compensating
cables of active screening systems of the magnetic field generated
by the several high voltage overhead transmission lines is given.